Clinical and laboratory COVID-19 features in hospitalized patients with concomitant diabetes mellitus type 2: A retrospective study - Arailym Abilbayeva; Anel Tarabayeva; Gulzhana Idrisova; Aigul Abdrakhmanova; Ainur Sadykova; Ravilya Yegemberdiyeva; Amangul Duisenova (National Scientific Medical Center, 2022)
Objective: To investigate the prevalence of diabetes mellitus in comorbidity structures and its effect on the clinical course in hospitalized COVID-19 patients in south region of Kazakhstan. Material and methods: A retrospective analysis of data from 918 patients with COVID-19 treated at the City Clinical Infectious Diseases Hospital was carried out. Pearson's Chi-square test and Student's t-test were conducted. Results: In Kazakhstan, diabetes mellitus occupies the second position in the structure of comorbidities in patients with COVID-19 with a share of 20%. Diabetes mellitus in patients most often occurs in combination with cardiovascular diseases and arterial hypertension (20.3% and 16.3%, respectively). Combination of diabetes mellitus, arterial hypertension and other diseases was detected in 72.4% of patients. Combination of diabetes mellitus, cardiovascular and other diseases was detected in 32.5%. In diabetes mellitus patients, COVID-19 was more severe, the hospital stay was longer, and patients over 60 years of age suffered. These patients had a combination of diabetes mellitus with arterial hypertension, obesity, and cardiovascular diseases. Hyperglycemia, elevated blood pressure, rapid breathing, and low saturation were more common for these patients. Conclusion: Diabetes mellitus ranks second in the structure of comorbidities in COVID-19 in the south region of Kazakhstan and is characterized by a combination with cardiovascular diseases, arterial hypertension and obesity. In patients with diabetes, COVID-19 is more severe, which affects the length of stay in the hospital, the mortality rate and the need for transfer to the Intensive Care Unit.